2019
DOI: 10.1177/1077699019886589
|View full text |Cite
|
Sign up to set email alerts
|

News in an Era of Content Confusion: Effects of News Use Motivations and Context on Native Advertising and Digital News Perceptions

Abstract: This study examined the effects of news use motivations and differing native advertising contexts (hard vs. soft news) on the ability to perceive commercialized content, evaluations of native advertising, and ensuing digital news perceptions. Based upon the framework of the persuasion knowledge model, an online experiment was conducted among a sample of U.S. adults ( N = 684). Engaging with news for informational motivations conditioned perceptions of advertising as did the contextual effects of hard versus so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
0
9
1
2
Order By: Relevance
“…Being forewarned about the covert advertising practices news organizations engage in can have an immediate chilling effect on engagement regardless of whether or not people perceive the content as journalism. While previous studies have shown the detrimental effect recognition of native advertising has on subsequent reporting by actual journalists (Amazeen, 2020; Iversen & Knudsen, 2019), the present finding demonstrates the risk publishers take when people simply hear about the practice of native advertising even in general. This merits further study.…”
Section: Discussioncontrasting
confidence: 87%
“…Being forewarned about the covert advertising practices news organizations engage in can have an immediate chilling effect on engagement regardless of whether or not people perceive the content as journalism. While previous studies have shown the detrimental effect recognition of native advertising has on subsequent reporting by actual journalists (Amazeen, 2020; Iversen & Knudsen, 2019), the present finding demonstrates the risk publishers take when people simply hear about the practice of native advertising even in general. This merits further study.…”
Section: Discussioncontrasting
confidence: 87%
“…When preparing to counter misinformation, it is important to identify likely sources. Although social media is an important misinformation vector 210 , traditional news organizations can promote misinformation via opinion pieces 211 , sponsored content 212 or uncritical repetition of politician statements 213 . Practitioners must anticipate the misinformation themes and ensure suitable fact-based alternative accounts are available for either prebunking or a quick debunking response.…”
Section: Implications For Practitionersmentioning
confidence: 99%
“…Implications for policymakers. Ultimately, even if practitioners and information consumers apply all of these strategies to reduce the impact of misinformation, their efforts will be stymied if media platforms continue to amplify misinformation 14,16,[208][209][210][211][212][213] . These platforms include social media platforms such as YouTube, which are geared towards maximizing engagement even if this means promoting misinformation 229 , and traditional media outlets such as television news channels, where misinformation can negatively impact audiences.…”
Section: ();mentioning
confidence: 99%
“…Einstein 2016) is partly due to the blending of a diverse range of content online, especially on social media. Content from journalistic organizations competes with promotional and user-generated content for audience attention (e.g., Amazeen 2020). Yet this phenomenon is equally due to the multiple roles that journalists may play in communicating on news sites as well as social media platforms.…”
Section: Discussion: Elements Of Trust and Distrustmentioning
confidence: 99%